Differences in pneumonia treatment between high-minority and low-minority neighborhoods with clinical decision support system implementation. (2nd April 2016) - Mitchell, Jordan; Probst, Janice C.; Bennett, Kevin J.; Glover, Saundra; Martin, Amy Brock; Hardin, James W.
Abstract : Background : The relationship between clinical decision support systems (CDSS) and quality is a relatively new, and in light of the new health information technology (HIT) legislation, policy-relevant area. Moreover, very few studies exist examining the link between HIT and healthcare disparities. The purpose of this article is to examine the association between CDSS and the treatment of pneumonia care within high-minority (≥29.1% non-White, non-Hispanic) and low-minority (<29.1%) Zip Code Tabulation Areas (ZCTAs). Research design : This study employed a cross-sectional design and used 2009 data from the American Hospital Association, the Centers for Medicare and Medicaid Services and the Research Triangle Institute. Adjusted analysis controlled for a hospital's propensity to use CDSS. Results : In the unadjusted analysis, hospitals in high-minority ZCTAs had lower pneumonia quality composite scores than their low-minority counterparts. When adjusting for other hospital and ZCTA-level variables, we found that CDSS use had stronger positive associations with quality in high-minority hospitals. Conclusions : Results support policy directives may support higher quality improvements by focusing CDSS adoption in high-minority hospitals.